2014
DOI: 10.1051/0004-6361/201424035
|View full text |Cite
|
Sign up to set email alerts
|

The role of cosmic rays on magnetic field diffusion and the formation of protostellar discs

Abstract: Context. The formation of protostellar discs is severely hampered by magnetic braking, as long as magnetic fields remain frozen in the gas. The latter condition depends on the levels of ionisation that characterise the innermost regions of a collapsing cloud. Aims. The chemistry of dense cloud cores and, in particular, the ionisation fraction is largely controlled by cosmic rays. The aim of this paper is to evaluate whether the attenuation of the flux of cosmic rays expected in the regions around a forming pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 53 publications
3
58
0
Order By: Relevance
“…The resulting flux of UV photons F UV (in the energy range between 11.2 and 13.6 eV) 4 More advanced models should take into account the fact that molecular clouds are magnetized and CRs gyrate along magnetic field lines in addition to being scattered by magnetic fluctuations on the scale of the particle gyroradius. For a detailed treatment of these effects, see Padovani & Galli (2011), Padovani et al (2013Padovani et al ( , 2014, and Morlino & Gabici (2015). 5 We note that the results presented in Section 3 practically do not depend on the precise form of the formula for x e .…”
Section: Local Radiation Fieldmentioning
confidence: 90%
“…The resulting flux of UV photons F UV (in the energy range between 11.2 and 13.6 eV) 4 More advanced models should take into account the fact that molecular clouds are magnetized and CRs gyrate along magnetic field lines in addition to being scattered by magnetic fluctuations on the scale of the particle gyroradius. For a detailed treatment of these effects, see Padovani & Galli (2011), Padovani et al (2013Padovani et al ( , 2014, and Morlino & Gabici (2015). 5 We note that the results presented in Section 3 practically do not depend on the precise form of the formula for x e .…”
Section: Local Radiation Fieldmentioning
confidence: 90%
“…Padovani & Galli (2011);Padovani et al (2013Padovani et al ( , 2014a found that mirroring always dominates focusing for a field topology obtained by ideal-MHD simulations of collapsing rotating clouds and that the ionisation rate could vary by up to a factor 50, depending on the mass-to-flux ratio and the magnetic flux tube considered. In addition, CR are partly absorbed by the dense medium, which lowers the CR ionisation rate (Padovani et al 2009).…”
Section: Cosmic-ray Ionisation Ratesmentioning
confidence: 99%
“…Padovani et al (2013Padovani et al ( , 2014 studied the propagation of CR along magnetic fields lines in collapsing cores, accounting for the effect of CR energy loss and magnetic mirroring. They show how CR ionisation rate is efficiently reduced in the central region because of the complex magnetic field lines configurations found in numerical models of protostellar collapse, making magnetic resistivities larger towards the cloud center.…”
Section: Limitationsmentioning
confidence: 99%